Managerial Strategies of Islamic Education Teachers in Implementing Religious Moderation in Educational Institution - Apriyani, Hikma; Agus Pahrudin; Husnilawati; Yuli Yanti; Achi Rinaldi; Ali Murtadho (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
The purpose of this research is to study the management methods used by Islamic Religious Education (PAI) teachers at SMKN 2 Bandar Lampung when implementing the values of religious moderation. The method of religious moderation emphasizes balance, tolerance, and an inclusive attitude in religious life. The researchers examined the role of PAI teachers as controllers in incorporating moderation values into the learning and school culture. They do this by using a qualitative case study approach. Observation, documentation, and in-depth interviews were used in the data collection process. The results show that PAI teachers at SMKN 2 Bandar Lampung use managerial strategies such as continuous value-based evaluation, internal teacher training, inclusive lesson planning, and cross-subject collaboration. Success is supported by the enhancement of the religious moderation curriculum, teacher training, and inclusive school policies. This research also applies a systems approach in educational management, considering the interaction between input, process, and output in moderate educational practices. The research results contribute to the development of contemporary Islamic education management theory and adaptive religious education policy practices. This research suggests that teachers should be strengthened with competency-based training and evaluation to implement the values of religious moderation in vocational schools.